Evaluasi Potensi Degradasi Lahan dengan Menggunakan Analisa Kemampuan Lahan dan Tekanan Penduduk terhadap Lahan Pertanian di Kecamatan Kokap Kabupaten Kulon Progo - Sartohadi, Junun (Universitas Muhammadiyah Surakarta, 2008)
Kokap sub district is located in Kulonprogo District, Yogyakarta Province. It has some problems of landslides and misuse of land. The research was proposed to determine the regions having potential of land degradation based on the land capability and population pressure analysis. This research was carried out using field survey. The field survey was based on landform unit as area sampling unit. The (Land Classification and Land Use Planning) LCLP software was applied for land capability classification. The Soemarwoto method was applied for the evaluation of population pressure on the agriculture land. The results of this research were: (1) land capability in the study area was varies from class II â class VII with limitation factors of slope, soil erodibility, soil texture, soil permeability and soil effective depth, (2) the whole study area fell into high population pressure class (that means it had exceed of its land capability), (3) most of the study area (51.9%) had been classified into high potential of land degradation.